Nutrition and development in Aboriginal and Torres Strait Islander children, using the LSIC Dataset - Thurber, K (My University, 2011)
The Longitudinal Study of Indigenous Children (LSIC), run by the Australian Government Department of Families, Housing, Community Services and Indigenous Affairs (FaHCSIA), is the first nation-wide longitudinal study to address the physical, emotional, social, and spiritual wellbeing of Aboriginal and Torres Strait Islander children in Australia. Previous research has demonstrated a clear link between early childhood nutrition and physical, intellectual, and behavioural development. Few studies, however, have examined this relationship within the Aboriginal and Torres Strait Islander populations of Australia. The current study, through the use of the LSIC dataset, aims to elucidate the relationship between the nutrition and development of today’s Aboriginal and Torres Strait Islander children. During Waves 1 and 2 of LSIC, a 24-hour food recall was administered to all children in the older cohort (aged 3.5 – 4.5 years in Wave 1, and 4.5 – 5.5 years in Wave 2), providing an indication of the types, though not quantity, of foods consumed. Data were also collected about children’s breastfeeding history, breakfast habits, and beverage consumption. In addition, researchers recorded the mothers’ food, alcohol, and smoking habits during pregnancy, thus creating a detailed nutritional profile for each child. The LSIC also provides several measures of physical, intellectual, and behavioural development for both study cohorts. Anthropomorphic data were collected for each child in the older cohort, with greater reliability in more recent waves of the study. Where data proves to be reliable, changes in weight-for-height percentile, height-for-age percentile, and BMI can be used to determine trends in children’s growth patterns. Subjective ratings of children’s health state, together with history of health service usage, can provide further information about the children’s physical health. The Renfrew Word Finding Vocabulary Test is administered to the older cohort to measure speech and language abilities, and the MacArthur Bates Communicative Development Inventory is used among the younger cohort (aged 0.5-1.5 years in Wave 1, and 1.5-2.5 years in Wave 2) to measure language development. Additionally, both cohorts complete some items adapted from the Parent’s Evaluation of Developmental Status (PEDS), a screening inventory designed to measure developmental and behavioral irregularities. An analysis of the associations between early childhood nutrition and these developmental outcomes will provide information critical for the development of effective nutritional intervention programs to be established within these communities.
Keywords: Child Development -- Cognitive; Child Development -- Physical; Childhood and child development; Child Development; Physical; Cognitive; Childhood and child development